Analisis Framing Pemberitaan Program Makan Siang Gratis Prabowo Gibran di Kumparan - A.Malik Haramain; Latif Ahmad Fauzan (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
The media plays a crucial role in shaping public opinion, including in reporting government policies. One of the widely discussed programs is Prabowo-Gibran’s free lunch initiative, which has garnered media attention. This study analyzes the framing of this program in the online media Kumparan during February 2024. Using a qualitative method with Pan & Kosicki’s framing analysis, it examines four framing structures in five selected news articles. The results show that Kumparan emphasizes the program’s urgency through government quotes (syntactic), applies the 5W+1H format focusing on benefits (script), frames it as a strategic policy (thematic), and reinforces a positive image with diction like "real solution" (rhetorical). This study highlights how media framing shapes public perception of government policies.